2003
DOI: 10.1034/j.1600-0838.2003.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Soccer injuries in childhood

Abstract: A prospective study of soccer injuries, involving 287 male youth players, from the ages of 12-15 was conducted in 24 Greek soccer clubs, during the course of one year. A total of 193 players sustained 209 injuries. The incidence of injuries was 4.0 injuries per 1000 h of soccer time per player, and the most common types of injuries were sprains and strains. Surprisingly, it was found that an increase of injury incidences occurred during practice. Fifty-eight injuries required medical assistance. The majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
4
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 17 publications
7
72
4
5
Order By: Relevance
“…This result is similar to that observed in 287 athletes from Greece aged between 12 and 15 years, who reported that 52.6% of their injuries occurred during training (29). Le Gall et al (21) observed in athletes aged between 14 and 16 years from France that 69.1% of injuries occurred during training, but with a significantly higher incidence in games than in trainings.…”
Section: Discussionsupporting
confidence: 76%
“…This result is similar to that observed in 287 athletes from Greece aged between 12 and 15 years, who reported that 52.6% of their injuries occurred during training (29). Le Gall et al (21) observed in athletes aged between 14 and 16 years from France that 69.1% of injuries occurred during training, but with a significantly higher incidence in games than in trainings.…”
Section: Discussionsupporting
confidence: 76%
“…The differences could be due to the various methodologies used to register injuries and exposures, the level of play (elite versus amateur) or the different age groups studied. For comparison the incidence in male youth players during seasonal play ranged from 5.4 to 11.2 injuries per 1000 match hour and 0.5 to 3.9 per 1000 training hours (Froholdt et al, 2009;Johnson et al, 2009;Le Gall et al, 2006;Kakavelakis, 2003). This was a lower incidence than reported for female youth football players.…”
Section: Female Youth Football Playersmentioning
confidence: 58%
“…No gender difference for injury incidence was found in either of the studies (Froholdt et al, 2009;Emery et al, 2005). The incidence for match play was higher for both elite male (Johnson et al, 2009;Le Gall et al, 2006) and female youth players (Le Gall et al, 2008) compared to amateur male (Froholdt et al, 2009;Kakavelakis et al, 2003) and female (Froholdt et al, 2009;Soligard et al, 2008;Steffen et al, 2007;Emery et al, 2005;Söderman et al, 2001a) players, but the incidence for training injuries were similar.…”
Section: Female Youth Football Playersmentioning
confidence: 84%
“…Raket sporlar› ve voleybol ile u¤raflanlarda s›kl›kla omuz ve dirsek sorunlar› görülürken, futbol ve basketbol oynayanlarda alt ekstremite yaralanmalar› birinci s›radad›r. Çocukluk ve ergenlik ça¤›nda ülkemizde en yayg›n spor dal› olan futbolda yaflanan sportif yaralanmalar›n %36-37,9'u dizde ve %24,5-29'u ayakbile¤inde görülmektedir (17,19). Bunlar› %9-22 ile uyluk, %5-6 ile bacak ve %5 ile pelvis-kas›k bölgesi yaralanmalar› takip etmektedir (14,17,19).…”
Section: Giriflunclassified